Upaya Peningkatan Keterampilan Berbicara Bahasa Inggris pada Pembelajaran Narrative melalui Drama Di Kelas XI IPA 4 Semester 1 SMA Negeri 1 Blora Tahun Pelajaran 2017/2018 - Bardiyono, Bardiyono (Sekolah Tinggi Agama Islam Muhammamdiyah Blora, 2017)
This classroom action research is intended to improve the student speaking skills of Grade 2 of Senior High School. It also to know more about the student's changes behaviour made by the students in the class after acting a role play. The subjects of this research were students Grade XI Science 4 of Senior High School 1 of Blora in 2017/2018. 30 students, consisting of 11 males and 19 females were selected as samples. Having identified the difficulties that the students faced in expressing and speaking English, a set of plan and actions in two cycles of research, covering planning, actions, observations and reflecting were formulated and then implemented. Individual cognitive tests, questionares, and observations were used to collect the date. The students' speaking skills were measured by scoring rubrict (Adopted from Agustin, H. Panduan Penilaian Kompetensi Inggris : 7-8). And then, the data were analized by the use of descriptive analitically technique.The result of the research indicated that through acting drama in narrative text learning, spoken cycles, the students could increase their speaking skill and the teaching learning process gets positive respond from the students.The result indicated that the students speaking skill has increased from 52.47% on the pra cycle, 61.96% on the first cycle, and 71.34% on the second cycle. It can be concluded that drama is an alternative technique to improve the students' speaking skill. Key Words : Speaking skill,Narrative,Drama